Effects of ASQ-based flipped learning on nurse practitioner learners' nursing skills, learning achievement and learning perceptions. (October 2019) - Lin, Hui-Chen; Hwang, Gwo-Jen; Hsu, Yaw-Don
Abstract: Training and examining healthcare practitioners' nursing skills by situating them in a contextualized environment to interact with trained simulated patients and making required decisions based on the collected information is a widely adopted approach in nursing training. In a nursing skills course, the flipped learning method shifts the lecture time to the before-class time, allowing more time for teachers' guidance and skills practice in the class. However, if students do not have in-depth understanding in the individual learning space, their learning achievement is often not as expected. In this study, an ASQ (Annotation, Summarizing and Questioning)-based flipped learning strategy for nursing skills training is proposed to engage nurse practitioners (NPs) in deep and effective learning. Moreover, an experiment was conducted to evaluate the effects of the proposed approach on learners' learning achievement, nursing skills, self-efficacy, cognitive load, and critical thinking tendency. The experimental results showed that the approach not only improved NPs' nursing skills, but also significantly increased their self-efficacy and critical thinking tendency. Highlights: An ASQ-based flipped learning approach was proposed. The approach helps students effectively identify key concepts before the class. An experiment was conducted in a clinical nursing skills training course. The approach improved the learners' nursing skills performance. The approach improved the learners' self-efficacy and critical thinking tendency.